The timeliness of recognizing accounting income in Malaysia: The influence of government linked companies transformation programme - Norman Mohd-Saleh,; Selamat Kundari,; Allias Alwi, (FEP, 2011)
This paper investigates the quality of financial reporting in Government Linked Companies (GLCs) and the effect of GLC’s transformation programme on the timeliness of accounting earnings in the Malaysian Market. This paper also compares the timeliness of earnings between the GLCs and Non-GLCs. This paper follows the model of Ball (2003) and estimates a linear pooled regression of accounting income on change in market value of equity during the period of 2004 to 2009. The method facilitates the determination of the timeliness of the accounting record to reflect economic gains or losses. The analysis shows that the quality of income in GLCs is higher than Non-GLCs. The results reveal that incremental economic losses sensitivity is more before the transformation programme compared to periods after the transformation programme and that economic gains recognition improves post year 2006 in GLCs. While there is an overall decline in the timeliness of losses recognition (in both GLC and Non-GLC groups), there is some improvement in the recognition of economic gains post year 2006. The results presented may be attributed to some transformation programmes implemented in GLCs and Non-GLCs. It is also acknowledged that the results could also be affected by the new IFRS implementation in year 2006. Yearly analysis reveals that there is no consistency in the effect of incremental economic losses sensitivity, which requires specific investigation into the incentives and specific forms of decisions in the future. While prior studies look at the timeliness of economic gains or losses recognition across countries, this paperattempts to investigate the issue of quality financial reporting in GLCs and how the implementation of the government transformation programme is able to have a significant impact on financial reporting in GLCs.